The Impact of Service Innovation on Passenger Satisfaction in Dubai Metro - Maryam Khalil Abbas Ahmad Alsaffar; Farah Laili Muda Ismail (USIM Press, 2025)
E-Proceeding Islamic Science Social Postgraduate Conference 2023 (ISSPeC 2023) “The Tradition of Knowledge as a Catalyst for the Sustainability of Civilization”/ editors : Anita Binti Ismail, Farah Laili Binti Muda @ Ismail, Kamal Azmi Bin Abd Rahman, Afi Roshezry Bin Abu Bakar, Ikmal Hafiz Bin Jamal Organized by: Institut Sains Islam (ISI) & Pusat Pengajian Teras (PPT) 30 November 2023